Using decomposition methodology to gain a better understanding of progress in and challenges facing regional and local climate action. (1st October 2018) - Newell, Robert; Robinson, John
Abstract: Decomposition analysis provides a potentially powerful means for analyzing community greenhouse gas (GHG) emissions data. However, this form of analysis is typically conducted at larger geographical scales (i.e., national and state/provincial levels), which leaves questions around how to apply this methodology to local and regional contexts. This study explores the application of decomposition methodology to community data in order to elucidate how this form of analysis can be employed to inform local/regional planning and climate policy. The research involved developing decomposition models that focus on two particularly areas important for local climate action - transportation and residential energy. Each model consisted of five factors - population, population distribution, travel (transportation) or energy customer accounts (residential) intensity, vehicle (transportation) or home energy (residential) type, and emissions intensity. Using data from the BC Community Energy Emissions Inventory, the study examined effects of the different factors on emissions changes occurring between 2007 and 2012 in the Metro Vancouver Regional District (British Columbia, Canada). Results from the transportation analysis indicated that population growth and people's choices in vehicle type had the effect of increasing emissions in the MVRD, whereas travel and emissions intensity factors had mitigating effects. The residential energy analysis indicated that only population effects led to emissions-increases in the MVRD, whereas the other factors had mitigating effects. Community-scale analyses also were conducted to identify municipalities where emissions-increasing effects were experienced more dramatically, for example, travel intensity effects in smaller communities (e.g., White Rock), energy accounts intensity effects in Vancouver, and emissions intensity effects in the District of North Vancouver. The study demonstrated how decomposition analysis can provide regional and local governments with valuable insight on what is contributing to GHG emissions and where progress is being made, which in turn can help these governments focus climate policy and planning efforts to achieve progress toward mitigation. The paper begins with an introduction on the use of decomposition methodology in energy and GHG emissions studies, and its potential value for analyzing local emissions data. The next sections discuss the analytical approach designed for and employed in this study, as well as describing the data used for this research. The paper then presents the results of the analysis performed on the MVRD. Finally, it concludes with a discussion on the implications of the results of this study for regional and local policy and planning. Highlights: We apply decomposition analysis to community greenhouse gas emissions data. Emissions changes between 2007 and 2012 in Metro Vancouver, BC, were examined. Decomposition models were developed for transportation and residential energy sectors. Both regional-scale and community-scale analyses were conducted. We discuss how decomposition analysis can inform regional and local climate action.